Implementation of Class Policy Based on the Reception of Vocational High School Teachers - Sukma, Dimas Pramata; Supriyanto, Teguh; Mardikantoro, Hari Bakti; Pristiwati, Rahayu (Newinera Publisher, 2025)
The role of teachers in shaping students’ character and ideology in Vocational High Schools (SMK) is essential, particularly in internalizing the values of heroism courage, sacrifice, integrity, and dedication. This study explores how gender differences among teachers influence classroom policy implementation as a medium for instilling the ideology of heroism. Using a qualitative descriptive approach and Moser’s research design (1989), the study analyzes how 50 SMK teachers (25 male and 25 female) in Tegal Regency respond to heroic values after reading Eko Prasetyo’s novel